Cystoid macular edema after cataract surgery : Cistoidni makularni edem nakon operacije katarakte - Merlak, Maja (Array, 2019)
Pseudophakic cystoid macular edema (PCME) is the most common complication of cataract surgery and is one of the possible causes of low visual acuity after cataract surgery. Various factors are implicated in its development but the core mechanism is likely surgically induced anterior segment inflammation that results in the release of endogenous inflammatory mediators. Anti-inflammatory medicines, including steroid and nonsteroid anti-inflammatory drugs, are postulated as having a role in both the prophylaxis and treatment of PCME. This article presents an updated review on the pathogenesis, risk factors, prophylaxis and treatment in PCME that reflect current research and practice.